OP31 RESTORE: Interim analysis of a Phase 2 study of QBECO SSI for the induction and maintenance of clinical and endoscopic remission in subjects with Moderate to Severe Crohn's Disease. (27th May 2021) - Bressler, B; Marshall, J K; Atkinson, K; Sutcliffe, S; Pankovich, J; Jones, M; Kalyan, S; Gunn, H
Abstract: Background: Innate immune defects play a role in the pathogenesis of CD. Enhancing innate immune competency and restoring mucosal barrier function provide a novel approach to treat CD. QBECO SSI is a first-in-class immunotherapy designed to correct innate immune dysfunction underlying CD. This analysis is from subjects in the open label portion of a planned controlled trial. Objectives were to assess endoscopic response at Wks 16 and 26, and select the optimal induction timepoint for the RCT. Safety and treatment compliance were also evaluated. Methods: 20 pts with moderate-to-severe CD were enrolled and received QBECO SSI by sc injection every other day for up to 52 wks. Minimum eligibility: Simple Endoscopic Score for CD (SES-CD) ≥7 (ileitis ≥4), abdominal pain (AP) score >21 (11-point scale) or liquid/very soft stools (SF) (BFS Type 6 or 7) >10 for 7 consecutive days during screening. Pts were evaluated for clinical symptoms and endoscopy at Wks 16, 26, and 52. After evaluation at the induction period (Wk 26) pts could continue in maintenance up to Wk 52. Endoscopies were evaluated by central blinded read and pts reported daily symptoms. Endoscopic response defined as ≥50% reduction in SES-CD from baseline. Clinical remission defined as AP and SF ≤21. Results: Mean age was 43.6 (SD 13.6) yrs; 60% men and 60% previously treated with biologics. Mean yrs since CD diagnosis was 14.4 (10.1), AP score 30.4 (15.8), SF score 36.2 (19.1) and mean SES-CD at baseline was 12.5 (6.7) indicating a more difficult to treat population. Endoscopic response rate by central read during the induction period was 30% (6/20) overall, 38% (3/8) for biologic naïve and 25% (3/12) biologic experienced pts (ITT analysis). Similar number of pts achieved endoscopic response at Wk 16 (4 pts) as 26 (3 pts). Mean SES-CD improved through Wk 26 with a 0.6 point greater reduction at Wk 26 compared to 16. Change in SES-CD from baseline in biologic naïve pts was -2.9 (5.8) at Wk 16 and -4.1 (6.7) at 26. Clinical remission was achieved by 45% (9/20) of pts at Wk 16 and 40% (8/20) at Wk 26; 16 pts continued into the maintenance phase of the study. By central evaluation, 13% (2/16) were in endoscopic response at Wk 52. QBECO SSI was very well tolerated. 8/20 (40%) pts reported AEs related to treatment. Most frequency reported related AE was injection site erythema (2/20, 10% pts). Majority of AEs were mild and no other related AE was reported by more than 1 patient. Conclusion: Week 26 was the optimal endoscopic evaluation timepoint for QBECO SSI treatment and will be utilized in the larger RCT. Both biologics naïve and experienced patients showed response to QBECO SSI treatment by Weeks 26 and 52, with higher response rates in biologics naïve patients. QBECO SSI was well tolerated.